Pentecostalism and 'National Culture': A Dialogue between Brazilian Social Sciences and the Anthropology of Christianity - Mariz, Cecília Loreto (Religion and society, 2011)
This article aims to show how the hegemonic interpretation of Pentecos- talism in Brazil has difficulty recognizing changes caused by these churches to 'local' cultures. We argue that this tendency can be explained by a widespread adherence to structuralist theories of society combined with an unwillingness to accept the reimag- ining of a national culture historically built up by Brazilian social science. We suggest that the Universal Church of the Kingdom of God has been the Pentecostal church most studied by Brazilian researchers because it provides a powerful means to indicate the strength of 'Brazilian culture'. Through our analysis of more recent studies, we point out the salience of these debates to wider questions relating to the emergent anthropology of Christianity, concluding that since neither discontinuities nor continuities can be denied in the field, the focus on one or the other dimension should be seen as a methodological choice rather than an orientation specifically arising from empirical observation.